Developing the Concept of Firm Success among Muslim SMEs in Malaysia: a Study of Islamic Religion Practices as Moderator - Nafisah Abdul Wahab, Nadratun; Othman, Shahrina; Binti Nasirun Hirun, Noraini; Abdul Ghani, Abdullah; Rushdi Idrus, Mohd (International Journal of Engineering and Technology, 2018)
This paper intended to develop the concept of firm success among Muslim SMEs in Malaysia. The researchers used entrepreneurial orientation multidimensional as independent variable (innovative, risk and proactive) to examine the relationship of these dimensions towards the success of Muslim SMEs by using Islamic religion practices as moderator. It is about developing the concept of Islamic success factors, as the failure of Muslim SMEs is alarming and the empirical references to Muslim SMEs success focusing on Islamic religion practices are limited. There were many attempts to connect entrepreneurial orientation to the Resource-Based View theory of firms. Resource-Based View, as underpinning theory, helps to describe the proposed research theoretical framework. Recent studies related to firm success have shown that entrepreneurial orientation is composed of innovation, risk and proactive having significant relationship with the firm success in the develop countries. However in Malaysia, there was only one study has documented the conceptual religiosity that influence relationship between entrepreneurial orientation and business success of entrepreneurs among the Malay community. The methodology for this study uses quantitative analysis, specifically, the Partial Least Squares Structural Equation Modelling (PLS-SEM) in processing the data. The population of the study is 2,286 PUNB (Perbadanan Usahawan Nasional Berhad) firms in Malaysia. Finally, this concept finding is able to facilitate future research proposals and to fill the knowledge gap in Resource-Based View concerning the relationship of Resource-Based View towards firm success. This study also contributed to the Resource-Based View literature on the perspective of Islamic religion practices as moderator.
Keywords: Firm Success; Muslim SMEs; Islamic Religion Practices; Malaysia